2016
DOI: 10.1111/acer.13000
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol: A Simple Nutrient with Complex Actions on Bone in the Adult Skeleton

Abstract: Background Alcohol is an important nonessential component of diet, but the overall impact of drinking on bone health, especially at moderate levels, is not well understood. Bone health is important because fractures greatly reduce quality of life and are a major cause of morbidity and mortality in the elderly. Regular alcohol consumption is most common following skeletal maturity, emphasizing the importance of understanding the skeletal consequences of drinking in adults. Method This review focuses on descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 188 publications
3
101
1
4
Order By: Relevance
“…Neither our study nor the Framingham study found a corresponding association in older men. One possible explanation could be that light to moderate alcohol consumption may affect bone beneficially in older individuals by slowing the rate of bone remodelling, while this effect is less certain in younger individuals [14]. Another possible explanation for the lack of an association in older men is selection bias, since a higher proportion of older heavy drinkers could have died before they reached the high-risk age for hip fracture, or they might have refrained from participating in the CONOR-studies because of poor health or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neither our study nor the Framingham study found a corresponding association in older men. One possible explanation could be that light to moderate alcohol consumption may affect bone beneficially in older individuals by slowing the rate of bone remodelling, while this effect is less certain in younger individuals [14]. Another possible explanation for the lack of an association in older men is selection bias, since a higher proportion of older heavy drinkers could have died before they reached the high-risk age for hip fracture, or they might have refrained from participating in the CONOR-studies because of poor health or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholism is a well-established risk factor for hip fractures because of increased risk of falling, poor nutritional status, poor functional status, more co-morbidities, disturbances in the bone remodelling system, impaired bone quality and adverse endocrine changes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Результаты большинства исследований указывают на увеличение под влиянием умеренных доз алкоголя мине-ральной плотности костей и снижение риска переломов, обусловленных остеопорозом [72][73][74]. Marrone et al изу-чали здоровых женщин в постменопаузе, употреблявших 19 ± 1 г этанола в день.…”
Section: остеопороз жкб деменция…unclassified